A rare co-existence of helicobacter pylori, candida albicans and candida keyfr in a giant gastric ulcer - Ali Tüzün İnce,; Orhan Kocaman,; Medina İsmailova,; Mukaddes Tozlu,; Zühal Gücin,; Meryem İraz, (Turkish Journal of Gastroenterology, 2019)
-